CRISPR and gene editing in HIV therapy: A scoping review - Tuta-Quintero, Eduardo; Martínez Ayala, Camila; Molina Ardila, Miguel Ángel; Sanabria Sarmiento, Rodrigo; Gonzalez Sotelo, Carlos Felipe; Cianci De León, Giannella; Pérez Mantilla, Daniela F.; Rhenals Acuña, Santiago; Collazos Bahamon, Estefanía; Mantilla Flórez, Yesid Fabian; Rueda Rodríguez, Alejandro; Pimentel, Juan (Gaceta Médica de Caracas, 2023)
Human immunodeficiency virus (HIV) is nowadays one of the major health problems worldwide. Several strategies have been explored for the eradication of latent HIV-1 reservoirs, current antiretroviral therapy stops the progression of HIV disease, however, as new therapies are being developed, CRISPR (clustered regularly interspaced short palindromic repeats) systems have recently been used as a genome editing technique. CRISPR is becoming progressively one of the possible cures, although it remains experimental, for HIV in medical research. This systematic review summarizes literature evidence of CRISPR gene editing in HIV/AIDS therapy. This study also identifies the research gaps in the current literature, helping to guide future research.